Analysis of Flood Inundation in the Surrounding Area of Retention Pond Control: The Case of Siti Khadijah Retention Pond, Palembang - M. Baitullah Al Amin (Journal of Regional and City Planning, 2016)
The area near the Siti Khadijah Palembang retention pond, especially Demang Lebar Daun street, is frequently inundated because of the overflowing of the retention pond, causing long traffic jams. This study aims to analyze the characteristics of flood inundation within the area for the existing situation and for a scenario of flood control using a pump system and an increase in open space. The flood routing within the retention pond was done using HEC-HMS software, while visualization of flood inundation was carried out using Global Mapper software. The results show that the capacity of the retention pond at this time is insufficient to accommodate run-off volume, whereas the flood peak discharge of 22.2 m3/s for a 5-year return period has the potential to inundate 11.09 Ha of the surrounding area. Flood control using pumps with a total capacity of 4 m3/s is able to reduce the inundation extent by 58.79%, while a 30% increase in  open space is only able to reduce the inundation extent by 15.33%. Furthermore, a combination of flood pumps and an increase in open space can reduce the inundation extent by 75.92%. Using this method results in a maximum inundation depth of less than 0.5 m with a potential inundation time of only 20 minutes, where Demang Lebar Daun street is no longer inundated. For short-term flood mitigation, there is a need to build a flood pump station at the Siti Khadijah retention pond , while for long-term mitigation there is a need to gradually and sustainably provide open space.Keywords. retention pond, HEC-HMS, flood routing, flood control.Abstrak. Kawasan di sekitar kolam retensi Siti Khadijah Palembang, terutama jalan Demang Lebar Daun sering mengalami genangan banjir akibat luapan air dari kolam retensi, sehingga menyebabkan kemacetan lalu-lintas yang cukup panjang. Penelitian ini bertujuan untuk menganalisis karakteristik genangan banjir di kawasan tersebut pada kondisi eksisting dan dengan skenario pengendalian menggunakan sistem pompa dan peningkatan luasan ruang terbuka hijau (RTH). Penelusuran banjir di kolam retensi dilakukan dengan bantuan program HEC-HMS, sedangkan visualisasi genangan banjir dilakukan dengan bantuan program Global Mapper. Hasil penelitian menunjukkan bahwa kapasitas kolam retensi saat ini sudah tidak mencukupi untuk menampung volume limpasan, dimana debit puncak banjir periode ulang 5 tahun sebesar 22,2 m3/s berpotensi menggenangi kawasan sekitar kolam dengan luasan mencapai 11,09 Ha. Pengendalian banjir menggunakan pompa berkapasitas total 4 m3/s mampu mereduksi luasan genangan sebesar 58,79%, sedangkan pengendalian banjir dengan peningkatan RTH sebesar 30% hanya mampu mereduksi luasan genangan sebesar 15,33%. Kombinasi pengendalian banjir menggunakan pompa banjir dan peningkatan RTH mampu mereduksi luasan genangan banjir sebesar 75,92%. Dengan metode pengendalian tersebut dihasilkan kedalaman genangan maksimum kurang dari 0,5 m dengan potensi lama genangan hanya selama 20 menit, dimana jalan Demang Lebar Daun tidak lagi tergenang. Untuk mitigasi banjir jangka pendek diperlukan pembangunan stasiun pompa banjir di kolam retensi Siti Khadijah, sedangkan untuk jangka panjang diperlukan penyediaan RTH yang dilakukan secara bertahap dan berkelanjutan.Kata kunci. kolam retensi, HEC-HMS, penelusuran banjir, pengendalian banjir.